2013
DOI: 10.1016/j.nano.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Radiative-surface plasmon resonance for the detection of apolipoprotein E in medical diagnostics applications

Abstract: In this study, a novel emission-based surface plasmon resonance platform using silver-coated optical fibers is described. Properly orienting antibodies on the surface enables rapid and specific detection of human apolipoprotein E (apoE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Application of a neutravidin solution onto the bare, i.e., unmodified, sensor surface for about 10 minutes led to a shift in resonance wavelength of about 500-600 pm ( Figure 13). A full monolayer of neutravidin has been reported to be roughly equivalent with a layer thickness of 3.5 nm [27], which is equivalent with a shift of about 800 pm, considering a surface sensitivity of 229 pm shift per nm layer thickness (Equation 3). The observed shift therefore is assumed to represent about 60-75% of a packed monolayer of neutravidin.…”
Section: Resultsmentioning
confidence: 99%
“…Application of a neutravidin solution onto the bare, i.e., unmodified, sensor surface for about 10 minutes led to a shift in resonance wavelength of about 500-600 pm ( Figure 13). A full monolayer of neutravidin has been reported to be roughly equivalent with a layer thickness of 3.5 nm [27], which is equivalent with a shift of about 800 pm, considering a surface sensitivity of 229 pm shift per nm layer thickness (Equation 3). The observed shift therefore is assumed to represent about 60-75% of a packed monolayer of neutravidin.…”
Section: Resultsmentioning
confidence: 99%
“…A white light LED (Thorlabs Inc., MCWHL2) was used for SPR analysis. A presence of significant surface roughness of the metal coating allowed for analysis of light scattered by surface plasmons directly above the sensor surface [25][26][27] instead of transmission measurements as it is done in conventional SPR fibre sensors [33]. PE layer deposition and dye attachment on the fiber samples were performed inside the flow cell and the SPR response was recorded at each step of the functionalization process.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the determined optimal surface roughness and the spacing between the fluorophore and the metal film, we demonstrate the fabrication of MEF based sensor on a side of a multimode optical fiber. It was previously reported that a fiber configuration with a rough silver coating could be used for fabrication of radiative Surface Plasmon Resonance (SPR) sensors that exploit scattering of the plasmonic wave [25][26][27]. Building on this SPR fiber sensing platform, we study the dependence of fluorescence intensity on the thickness of the silver films and discuss advantages and limitations of the MEF fiber sensor.…”
Section: Introductionmentioning
confidence: 99%
“…For such applications it is necessary to immobilize sensor molecules on the glass surface of the MOF exposed core, which can then be used directly within the medium as a sensor without requiring prior pre-mixing of analyte with sensor molecules. Functionalization methods traditionally used include silanes [7,8] or polyelectrolytes [9,10], which provide a functional group on the surface to which the sensor molecules can be covalently attached. These processes require several steps that typically take many hours to perform, due to the incubation times needed to achieve consistent maximized binding efficiency [8,10].…”
Section: Introductionmentioning
confidence: 99%